Difficulties in spontaneously performing level 2 perspective-taking skills in children with autism spectrum disorder. Issue 4 (30th April 2019) - Asaoka, Hiroshi; Takahashi, Tomoya; Chen, Jiafei; Fujiwara, Aya; Watanabe, Masataka; Noro, Fumiyuki
Abstract : Purpose: The purpose of this paper is to investigate why children with autism spectrum disorder (ASD) tend to respond to tasks from their own perspective. The authors investigated the effects of explicitness of viewpoint on performance of spontaneous level 2 perspective-taking skills in six- to eight-year-old children with ASD. Design/methodology/approach: The authors conducted visual perspective-taking tasks with explicit and implicit instructions about the viewpoint to be used. Participants operated a toy car on a map while listening to the experimenter's instructions. In the implicit condition, when the experimenter said "Turn right/left" at each intersection, the participants moved the car accordingly. Subsequently, in the explicit condition, the experimenter said "Look from the driver's viewpoint and turn right/left" at each intersection. Findings: In the implicit condition, the authors did not observe a clear developmental change in performance between six- and eight-year-old children in the ASD group. In contrast, performance in the ASD group improved under the explicit condition relative to that under the implicit condition. Originality/value: The results suggest six- to eight-year-old children with ASD tend not to spontaneously use level 2 perspective-taking skills. Therefore, viewpoints should be explicitly instructed to children with ASD. In addition, it is also important to implement training to encourage spontaneous transitions from self-perspective to other-perspective under the implicit condition.